2014
DOI: 10.1158/1538-7445.am2014-1971
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1971: Inhibition of CXCR4 pathway augments trastuzumab sensitivity in HER2 positive breast cancer cells with intrinsic and acquired trastuzumab resistance

Abstract: The clinical benefit from trastuzumab (T) in HER2-positive breast cancers is limited by de novo or acquired resistance. By serial exposure of HER2+ breast cancer cell lines BT474 and SKBr3 to T at 200 µg/ml for 1 year and clonogenic selection, we have developed T-resistant cell lines and identified differentially expressing genes including consistent overexpression of CXCR4 at the mRNA and protein levels. CXCR4 is involved in breast cancer metastasis and proliferation and its overexpression in human breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…In our previous studies, by establishing and using trastuzumab-resistant breast cancer cell models, we initially found upregulation of C-X-C motif chemokine receptor 4 (CXCR4), a G protein-coupled receptor of stromal cell-derived factor-1 (SDF-1; CXCL12) in trastuzumab-resistant breast cancer. Knockdown of CXCR4 with shRNA sensitized the cells to trastuzumab [18][19][20]. Consistent with our ndings, a very recent clinical study showed increased CXCR4 expression in trastuzumab-resistant breast cancer tissues and was associated with a higher risk of recurrence [21].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our previous studies, by establishing and using trastuzumab-resistant breast cancer cell models, we initially found upregulation of C-X-C motif chemokine receptor 4 (CXCR4), a G protein-coupled receptor of stromal cell-derived factor-1 (SDF-1; CXCL12) in trastuzumab-resistant breast cancer. Knockdown of CXCR4 with shRNA sensitized the cells to trastuzumab [18][19][20]. Consistent with our ndings, a very recent clinical study showed increased CXCR4 expression in trastuzumab-resistant breast cancer tissues and was associated with a higher risk of recurrence [21].…”
Section: Introductionsupporting
confidence: 88%
“…We previously showed upregulation of CXCR4 is involved as a driver of trastuzumab resistance in HER2+ breast cancer cells [18][19][20]. In the current study, we demonstrated that the increased CXCR4 expression is associated with cell cycle progression and reaches a peak in the G2/M phases.…”
Section: Discussionsupporting
confidence: 63%